2017
DOI: 10.1007/s11010-017-3054-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of MCP-1 and IL-6 in combination predict the presence of coronary artery disease and mortality in subjects undergoing coronary angiography

Abstract: Cytokines play a key role in the pathogenesis of coronary artery disease (CAD). The aim of current study was to investigate the relationship between the serum concentrations of 12 cytokines with mortality and extent of CAD in individuals undergoing angiography and healthy controls. 342 CAD patients were recruited and divided into 2 groups: those with ≥50% occlusion in at least one coronary artery [Angiography (+)] or <50% obstruction in coronary arteries [Angiography (-)]. Also 120 healthy subjects were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…This hypothesis was confirmed in our clinical and in vivo study as well as our previous in vitro research [ 12 ]. More importantly, in this in vivo study, we not only analyzed the IL-6, TNF- α , IL-10, and TGF- β in plasma and tissues of ApoE-/- mice as in vitro experiments but also included the detection of MCP-1 and IL-1 β which are implicated to be particularly important biomarkers for CAD diagnosis and mortality prediction [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was confirmed in our clinical and in vivo study as well as our previous in vitro research [ 12 ]. More importantly, in this in vivo study, we not only analyzed the IL-6, TNF- α , IL-10, and TGF- β in plasma and tissues of ApoE-/- mice as in vitro experiments but also included the detection of MCP-1 and IL-1 β which are implicated to be particularly important biomarkers for CAD diagnosis and mortality prediction [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was confirmed in our clinical and in vivo study as well as our previous in vitro research [12]. More importantly, in this in vivo study, we not only analyzed the IL-6, TNF-α, IL-10, and TGF-β in plasma and tissues of ApoE-/-mice as in vitro experiments but also included the detection of MCP-1 and IL-1β which are implicated to be particularly important biomarkers for CAD diagnosis and mortality prediction [28,29]. Furthermore, our present study also showed upregulated miR-16 may exert anti-inflammatory roles in AS by suppressing the transcription of PDCD4 and then activated p38 and ERK1/2, but inactivated the JNK pathway.…”
mentioning
confidence: 99%
“…The results confirmed that the relative expression of miR-126 was negatively associated with the Gensini score, suggesting a reverse correlation of miR-126 with the severity of CAD. Furthermore, inflammatory cytokines are also reported to be positively correlated with the disease severity [41,42,43]. The reverse correlation of miR-126 with Gensini score might be explained as follows: (1) as an anti-inflammatory factor, miR-126 suppress inflammatory responses, possibly through downregulating inflammatory cytokines and upregulating anti-inflammatory cytokines [31,32,33]; (2) miR-126 could decrease the endothelial function-related molecules, including VEGF, ICAM-1, and VEGF [31,38,39,44].…”
Section: Discussionmentioning
confidence: 99%
“…Эти исследования ведутся для выделения лиц с высо-ким риском осложненного течения сердечно-сосудистой патологии, а также для стратификации риска у условно здоровых лиц. Сегодня в литературе можно найти результаты исследований таких биомаркеров, как трансформирующий фактор роста бета (TGF-beta1) [34], молекулы клеточной адгезии (САМ) [35], моноцитарный хемоаттрактантный белок-1 (МСР-1) [36], фактор стромальных клеток 1a (SDF-1a) [37], лектиноподобный рецептор окисленных липопротеинов низкой плотности 1 (LOX-1) [38], пентраксин 3 (PTX3) [39], а также билирубин [40,41] и гликированный гемоглобин A1c (HbA 1c ) [42], чьи концентрации в сыворотке и/или плазме крови, по ряду исследовательских работ, возможно, связаны с наличием и тяжестью ИБС.…”
Section: биомаркеры биохимического уровняunclassified